Isyarat-isyarat Manajemen Mutu Pendidikan Dalam Al-Qur’an dan Al-Hadits - Tio Ari Laksono (Southeast Asian Journal of Islamic Education Management, 2021)
Abstract Quality is conformance to requirement, that is, a product is said to be of quality when it has reached the agreed standard target. This research examines the quality cues found in the sources of Islamic law, namely the Al-Quran and al-hadith. To strengthen the quality management of education according to the perceptions of legal sources and Muslim scholars. The data collection process was carried out through library research. Something is said to have quality when something has a good meaning and vice versa. In the context of education, if someone says a school is a quality, it can be interpreted that the graduates are quality, the teachers are qualified, the building is proper, and so on. To mark something that has quality or not, someone gives symbols with certain names, for example, superior schools, model schools, pilot schools, and so on. Quality is the realization of Ihsan's teachings, which is to do good to all parties because Allah has done well to humans with His various favors, and is prohibited from doing damage in any form.   Keywords: Education Quality Management, Al-Quran, Al-Hadith   Abstrak Mutu merupakan conformance to requirement, yaitu produk dikatakan berkualitas ketika sudah mencapai target standar yang di sepakati. Penelitian ini mengkaji isyarat mutu yang terdapat pada sumber hukum umat islam yaitu al-quran dan al-hadits. Dengan tujuan memperkuat manajemen mutu pendidikan menurut persepsi sumber hukum dan para ahli muslim. Proses pengumpulan data dilakukan melalui studi pustaka (Library Research). Sesuatu itu dikatakan bermutu ketika sesuatu itu mengandung makna yang baik dan sebaliknya. Dalam konteks pendidikan, apabila seseorang mengatakan sekolah itu bermutu, maka bisa dimaknai bahwa lulusannya berkualitas, gurunya mumpuni, gedungnya layak, dan sebagainya. Untuk menandai sesuatu itu bermutu atau tidak seseorang memberikan simbol-simbol dengan sebutan-sebutan tertentu, misalnya sekolah unggulan, sekolah teladan, sekolah percontohan dan lain sebagainya. Mutu merupakan realisasi dari ajaran ihsan, yakni berbuat baik kepada semua pihak disebabkan karena Allah telah berbuat baik kepada manusia dengan aneka nikmat-Nya, dan dilarang berbuat kerusakan dalam bentuk apapun.   Kata Kunci: Manajemen Mutu Pendidikan, Al-Quran, Al-Hadits